Influence Law International to Policy National Law in Developing Countries in Right Basic Man - Sunarto, Atika; Rumapea, Mazmur Septian; Adnan, Muhammad Ali; Khair, Azizan (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The issue of the relationship between international law and national legal policies in developing countries, especially in the context of human rights (HAM), is increasingly relevant in contemporary international law studies. Developing countries often face significant challenges in integrating international human rights standards into their domestic legal systems.Purposes of the Research: This study aims to analyze the influence of international law on national legal policies in developing countries in the context of human rights.Methods of the Research: The method used in this study is the normative legal research method with a literature study approach, which includes an analysis of various national laws and international legal instruments related to human rights. In addition, this study also refers to the results of academic studies, reports from international human rights institutions, and official documents from organizations such as the United Nations (UN) and the National Human Rights Commission. This approach provides a more comprehensive picture of the implementation of international human rights standards in developing countries.Results Main Findings of the Research: The results main findings of the study show that although many developing countries have ratified various international instruments, such as the Universal Declaration of Human Rights and the International Covenant on Civil and Political Rights, their implementation is often hampered by various domestic factors. Inconsistencies between international obligations and national conditions are major obstacles, exacerbated by political instability, weak state institutions, limited resources, and tensions between international norms and local cultures. In addition, political resistance to the implementation of international human rights policies is also a significant challenge, especially in countries that prioritize political or economic interests over commitment to global human rights standards.